2018
DOI: 10.1111/ajo.12849
|View full text |Cite
|
Sign up to set email alerts
|

The burden of adverse obstetric and perinatal outcomes from maternal smoking in an Australian cohort

Abstract: Women who smoke in pregnancy have worse obstetric and perinatal outcomes compared to controls and should be managed as high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
2
10
2
1
Order By: Relevance
“…The rate of NICU admission was similar between the study groups. Similar results were shown by Kharkova and colleagues (2017) [18], though another study found a significant increase in NICU admission in the smoking cohort [20]. Thus, we cannot accept smoking as the only factor that affects the Apgar score and the need for NICU admission [35].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The rate of NICU admission was similar between the study groups. Similar results were shown by Kharkova and colleagues (2017) [18], though another study found a significant increase in NICU admission in the smoking cohort [20]. Thus, we cannot accept smoking as the only factor that affects the Apgar score and the need for NICU admission [35].…”
Section: Discussionsupporting
confidence: 73%
“…According to Li and colleagues (2019), smoking women were more likely to have a caesarean section for nonreassuring fetal status [20]. However, in our study, there were no differences in the mode of delivery between women despite their smoking status.…”
Section: Discussioncontrasting
confidence: 72%
“…Maternal smoking, as a confounder, is associated with prematurity, low birth weight and cleft lip, 24,25 characteristics that may be present in the classification of neonatal near miss cases and these are also related to a longer hospitalization. Additionally, smoking itself leads to a higher frequency of neonatal hospitalization, 26 and a higher incidence of pulmonary bronchodysplasia which increases hospitalization length. 27 As the main exposure, our definition of neonatal near miss in this study was validated with the research data (sensitivity: 92.5% and specificity: 97.1%).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that smoking [22,23] and illicit drug use during pregnancy [24,25] are associated with several adverse perinatal outcomes. In Australia, indigenous women have significantly poorer neonatal outcomes attributable to smoking, alcohol and substance misuse, and assault [26].…”
Section: Discussionmentioning
confidence: 99%